Teacher training model - towards a Collaborative Rubric Bank - Espinoza-Guzmán, Julia; Gamboa-Camacho, Pablo; Chacón-Rivas, Mario (IEEE, 2017)
Beyond providing alternatives to build rubrics, a group of researchers in Tecnológico de Costa Rica found the need to implement best practices in the definition and validation of evaluation rubrics, to encourage the creation of a Higher Education bank of assessment instruments. To achieve this goal, in the Tecnológico de Costa Rica, a teacher training process was established, which includes cooperative-collaborative work, scaffolding for the construction of knowledge and assessment tests carried out in the institutional LMS. The ultimate purpose is to build skills in teachers to design more robust rubrics and thus to form an institutional bank of evaluation instruments to share among colleagues. The first results meet the expectations established for the training model, as well as those of the teachers who participate in the training and use the rubrics for evaluation in their courses, as shown in the paper.
© © 2017 IEEE. Personal use of this material is permitted. Permission from IEEE must be obtained for all other uses, in any current or future media, including reprinting/republishing this material for advertising or promotional purposes, creating new collective works, for resale or redistribution to servers or lists, or reuse of any copyrighted component of this work in other works.
Keywords: Entrenamiento; Instrumentos; Software; Servicios médicos; Educación; Cursos